Pressure-resisting capability of the knot area of the primary barrier for a LNG containment system. (1st February 2015) - Lee, Dongyoung; Kim, Ki Hyun; Choi, Ilbeom; Lee, Dai Gil
Abstract: Stainless steel corrugations of the primary barriers of a liquefied natural gas (LNG) containment system have been supported with pressure-resisting structures (PRS) composed of an aluminum and glass fiber composite to improve their buckling resistance against shock loading due to LNG cavitation. Because the knot area is composed of two corrugations and is not reinforced due to its complicated shape, its pressure-resisting capability may be lower than that of the corrugations. In this study, new hydraulic test equipment has been developed with butyl rubber to evaluate the pressure-resisting capability of the knot area of the primary barrier. In addition, the pressure-resisting capabilities of the knot area with and without PRS under the corrugation near the knot area will be investigated. Highlights: Hydraulic test equipment for knot area is developed. Pressure-resisting capability of the knot area is measured. A failure criterion of the knot area is established. PRS increase the pressure-resisting capability of the knot area. Glass composite PRS deforms less than aluminum PRS.